Influential Article Review - How Online Retailers Differential and Price Products - Flores, Irma; Butler, Joe (Journal of Marketing Development and Competitiveness, 2019)
This paper examines marketing. We present insights from a highly influential paper. Here are the highlights from this paper: This study aims to contribute to marketing theory by applying monopolistic competition theory to investigate how differentiation affects online retailers’ pricing power. We examine the intermediary effect of customer loyalty on the relationship between differentiation and pricing power of online retailers. We assume that customers have different preferences for the differentiated characteristics of online retailers, and thus different degrees of willingness to pay premiums, which gives online retailers pricing power. Structural equation modeling (SEM) is employed to test the hypothesized relationships between differentiation, customer loyalty, and pricing power. The statistical results of the empirical data indicate that some of the differentiation characteristics of online retailers can cultivate their pricing power indirectly. Logistics quality followed by commodity assortment and transaction security produces profound effects on the buildup of pricing power with customer loyalty as an intermediary factor. Results further reveal that commodity quality is positively related to pricing power. This study expands the definition of differentiation by combining corporate strategic positioning with commodity pricing. Implications for practice and directions for future research are provided. For our overseas readers, we then present the insights from this paper in Spanish, French, Portuguese, and German.